Mental models of university quality in San Marcos students - Orellana Manrique, Oswaldo (2006)
Investigation takes as reference the contributions from Cognitiva Psychologist on mental models, in the proposals of Johnson-Laird (1996), Moreira (1997) and Vergnaud (1996), as well as construction cognitive of the concept of university quality in its different dimensions and proposals. The investigation is exploratory, descriptive and comparative. The objectives of investigation are the following ones: 1. Identify and to characterize the mental models developed by the university students, 2. Determine the characteristics and attributes and to compare them in the five academics areas who organize the studies in Universidad Nacional Mayor de San Marcos. We have developed the analysis method of content, based in connotative meanings of quality, by selecting concepts accepted in technical approaches and representations made by the students. It has identified eighteen parameters of quality with three levels classified in each one. The mental model is induced by the argumentales theoric constructions accepted by conceptual systems and common knowledge. The finding of investigation centralizes in the peculiarities of the mental model that have the students in each one of the implied criminals in the study, selected five parameters for the present effects of it publication. Investigacin establishes one comparacin in construccin of the mental models about the university quality in five academic areas in reference.